2020
DOI: 10.1007/s42452-020-3038-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of metal soap formation in historical oil paintings: the influence of fatty acid concentration and nucleus geometry on the induced chemo-mechanical damage

Abstract: Metal soap formation is one of the most widespread degradation mechanisms observed in historical oil paintings, affecting works of art from museum collections worldwide. Metal soaps develop from a chemical reaction between metal ions present in the pigments and saturated fatty acids, which are released by the oil binder. The presence of large metal soap crystals inside paint layers or at the paint surface can be detrimental for the visual appearance of artworks. Moreover, metal soaps can possibly trigger mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The fracture properties of the paint and crystallised metal soap are derived from the stress-strain diagram reported in Fuster-Lรณpez et al ( 2016), leading to an ultimate tensile strength ๐‘ก u 1 = 2.2 N/mm 2 and a mode I fracture toughness ๐บ I,c = 0.418 N/mm. From the simulation results presented in Eumelen et al (2021), it can be observed that the fracture process in the painting is indeed dominated by mode I cracking events. Therefore, the fracture properties in mode II are expected to only have a minor influence on the computational results, and, for simplicity, are taken equal to the properties under mode I conditions, i.e., ๐‘ก u 2 = ๐‘ก u 1 = 2.2 N/mm 2 and ๐บ II,c = ๐บ I,c = 0.418 N/mm.…”
Section: Materials Propertiesmentioning
confidence: 98%
See 4 more Smart Citations
“…The fracture properties of the paint and crystallised metal soap are derived from the stress-strain diagram reported in Fuster-Lรณpez et al ( 2016), leading to an ultimate tensile strength ๐‘ก u 1 = 2.2 N/mm 2 and a mode I fracture toughness ๐บ I,c = 0.418 N/mm. From the simulation results presented in Eumelen et al (2021), it can be observed that the fracture process in the painting is indeed dominated by mode I cracking events. Therefore, the fracture properties in mode II are expected to only have a minor influence on the computational results, and, for simplicity, are taken equal to the properties under mode I conditions, i.e., ๐‘ก u 2 = ๐‘ก u 1 = 2.2 N/mm 2 and ๐บ II,c = ๐บ I,c = 0.418 N/mm.…”
Section: Materials Propertiesmentioning
confidence: 98%
“…This modelling strategy was originally proposed in Xu and Needleman (1994), and allows for the robust simulation of crack patterns at arbitrary locations and in arbitrary directions. It naturally includes the effects of crack bifurcation, crack branching and crack coalescence, as previously demonstrated for applications related to historical paints (Eumelen et al, 2019(Eumelen et al, , 2020(Eumelen et al, , 2021, wood (Luimes et al, 2018;Scheperboer et al, 2019;Luimes and Suiker, 2021), polymers (Tijssens et al, 2000), fibrous composites (Cid Alfaro et al, 2010a,b;Geng and Suiker, 2019) and cementitious materials (Scheperboer et al, 2021). The interface elements are characterised by the interface damage model proposed in Cid Alfaro et al (2009).…”
Section: Interface Damage Modelmentioning
confidence: 99%
See 3 more Smart Citations